Knowledge, attitudes and practices of nurses regarding obesity in private healthcare institutions in Oshana region, Namibia - Moyo, Perseverance (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.